MORPHOSTRUCTURE OF THE EGYPTIAN CONTINENTAL MARGIN: INSIGHTS FROM SWATH BATHYMETRY SURVEYS - Mascle J.; Sardou O.; Migeon S.; Caméra L.; Loncke L.; Gaullier V. (My University, 2006)
In the Eastern Mediterranean, offshore Egypt, the Nile continental margin is characterized by a large deep water turbiditic system known as the Nile Deep Sea Fan. This post-Miocene terrigenous construction covers an approximately 10 km-thick sedimentary pile, including 1-3 km of Messinian salt layers. Systematically collected swath bathymetric data proved to be the most powerful tool to discover, describe and study many sea floor features of this sedimentary construction which reflects competition between active tectonic, sedimentary, and geochemical processes. Gravity tectonics, triggered by underlying mobile salt layers, construction of channel-levee systems, the passage of turbidite flows, sedimentary slope failures at various scales, massive mud expulsions and fluid seepages are all interfering to shape the Nile Deep Sea Fan seabed. © Springer 2006.
Keywords: MORPHOLOGY; NILE CONTINENTAL MARGIN; SEA FLOOR PROCESSES; SWATH BATHYMETRY; Messinian; Cenozoic::Neogene::Miocene::Messinian; Кайнозой::Неоген::Миоцен::Мессинский